A investigação em arquitetura a partir da geometria gráfica: um estudo de revisão sistemática e de abordagem didática - Conceição, Sandro Martinez (2020)
Analytical methods, supported by graphic geometry, help to explain the types of formal organizations employed in a design process and/or architectural construction process. Several studies, throughout history, have submitted works and landscapes to this type of method for the construction of knowledge about architectural and urbanistic practice. With didactic interest, in this study, a systematic review of a specific journal in the area of architectural representation is carried out, to observe the incidence of using such methods in the current scientific production. It seeks to comprehend what types of knowledge these methods may be associated with, how they have been referenced on researches and how they are being affected in the face of the advancement of digital technologies of representation. The structured notion of knowledge, from Yves Chevallard's Anthropological Theory of Didactics, is employed to identify the elements that compose the methods used, and what are the types of associated problems, technologies and theories. The results include a reflection on the terminology used to featuring both methods and the recognition of a repertoire of knowledge elements associated with them. Among the architectural problems, it seems notorious those of project authorship elucidation, of stylistic influences, and of the very explanation of compositional rules to activate creative processes. A repertoire of technologies related to photogrammetry and 3D scanning is identified, which gives precision and agility to graphic geometric analysis. A repertoire of technologies related to photogrammetry and 3D scanning is identified, conferring precision and agility to graphic-geometric analysis. Under a didactic approach, this work can contribute to curriculum revision processes, by highlighting, especially, the connections with the different fields of knowledge that graphic geometry, now enhanced with advanced technologies of representation, contributes to the construction of architectural knowledge.